Using ground-based fixed and mobile weather radars and numerical modeling to evaluate hurricane structure and dynamics at landfall - Alford, Austin (My University, 2021)
Hurricane observations during landfall in the United States have received relatively little attention in the research community compared to hurricanes observed over the open ocean. Aircraft-based observations using in situ and remotely sensed data have elucidated much about the structure and evolution of hurricanes. However, gathering high temporal (3-5 minutes) and high spatial (500-1000 m) resolution observations over contiguous spatial domains (e.g., 10,000 km2) is not possible with aircraft due to instrumentation limitations, operational missions, and required flight paths in hurricanes. Using ground-based fixed and mobile Doppler weather radars afford continuous observations of processes that not only affect landfall, but also offer comparison to aircraft observations of processes that occur over the open ocean. In addition, hurricane landfalls have generally been under sampled due to aircraft observations being relegated to the open ocean for crew and aircraft safety. The Shared Mobile Atmospheric Research and Teaching (SMART) Radars (SRs) are a pair of mobile Doppler, dual-polarization radars operated by the University of Oklahoma. Having sampled 14 landfalling tropical storms and hurricanes, datasets collected by the SRs likely provide key insight into hurricane dynamics and is the primary data source of this work. SR data, along with other fixed ground-based radars, in situ platforms, and satellite remote sensing, are combined to provide a comprehensive view of hurricane structure using dual-Doppler analysis, single Doppler observations, microphysical retrievals, and surface station network wind mapping. The primary datasets for this analysis includes Hurricanes Isabel (2003), Irene (2011), Matthew (2016), and Harvey (2017). This dissertation presents a detailed analysis of asymmetric dynamic processes in the form of the excitation of vortex Rossby waves from asymmetric convection in the eye in landfalling hurricanes and their impacts on the surface winds and rainfall experienced at landfall. Specifically, the verification of vortex Rossby wave theory is addressed by examining the propagation of rainbands radially outward of the hurricane eyewall. The impact of vortex Rossby waves on the symmetrization and intensity change in hurricanes is also assessed for the first time in high temporal and spatial resolution. The microphysical structure of vortex Rossby wave-induced rainbands through remotely sensed and in situ observations is also detailed. As vortex Rossby wave-driven processes are currently not well understood, this work concludes by examining a numerical simulation of Hurricane Harvey (2017) to compare observed vortex Rossby waves to those in this simulation. Additionally, little is known regarding the evolution of the hurricane boundary layer at landfall. In order to assess the impacts of structures in the wind field arising from asymmetric dynamics, the hurricane boundary layer response to a step-function change in aerodynamic surface roughness inland must be understood. Using aircraft observations offshore and ground-based mobile and fixed radars onshore, the hurricane boundary layer is quantitatively examined, for the first time, from over the open ocean through the coastal transition. The verification of boundary layer models, which can be used to estimate surface winds from winds observed aloft, is vital the estimation of standardized surface winds. The transfer of momentum by turbulence on a variety of spatial scales can be examined to understand the evolution of the hurricane wind field aloft and relate it to surface winds observed in situ.
Keywords: Hurricane; Weather Radar; Wind Hazards; Dynamics